An idea to efficiently recover the waste heat of Data Centers by constructing an integrated system with carbon dioxide heat pump, mechanical subcooling cycle and lithium bromide-water absorption refrigeration cycle - Lin, Xinxing; Zuo, Lujie; Yin, Likun; Su, Wen; Ou, Shaoduan (Energy conversion and management, 2022)
•An integrated system is proposed to recover the waste heat of Data Centers.•Energy, exergy and economic performance are analyzed for the system.•Performances of pure and mixture refrigerants are discussed. As a perennial stable heat source, Data Centers release a continuous increasing amount of waste heat. Besides rejecting it into atmosphere by traditional refrigeration ways, how to effectively utilize the waste heat is still an open question. Thus, an idea is proposed to integrate carbon dioxide heat pump with mechanical subcooling cycle and lithium bromide-water absorption refrigeration cycle for the waste heat recovery of Data Centers. The carbon dioxide heat pump is firstly used for upgrading the low-temperature heat of Data Centers, and then the hot water from heat pump is employed to supply heat in winter, drive lithium bromide-water absorption refrigeration cycle in summer for surrounding office buildings. The main function of mechanical subcooling cycle is to increase the cooling capacity of carbon dioxide heat pump, and decrease the required mass flow of carbon dioxide in the Data Centers cooling. For this integrated system, energy, exergy and economic models are respectively established with the help of MATLAB and REFPROP 10 to obtain the corresponding performance. Eight high-temperature mixtures, namely R600a/R601a, R600a/R134a, R600a/R1234yf, R600a/R152a, R600a/R1233zd, R600a /R1234ze and R600a/R236ea, are considered in the mechanical subcooling cycle. The obtained results indicate that the optimum mixture is R600a/R601a (0.4/0.6) with the highest coefficient of performance 2.12 under the discussed conditions, but R600a/R134a (0.5/0.5) with coefficient of performance 2.01 is more recommended out of security. On this basis, exergy destruction and economic analysis are conducted for the use of R134a, R600a and R600a/R134a (0.5/0.5) in mechanical subcooling cycle. Compared with pure fluids R600a and R134a, the exergy destruction of mixture R600a/R134a (0.5/0.5) could be reduced by 593.1 kW ∼ 1114 kW. Besides, the required heat exchanging area of condenser could be diminished by 19.20%∼23.16%. As for the economy, the cost of lithium bromide-water absorption refrigeration unit takes up over the half of the integrated system cost. For different working fluids in mechanical subcooling cycle, the payback period of developed system ranges from 2.04 to 2.46 years.